Validation of Monilinia fructicola Putative Effector Genes in Different Host Peach (Prunus persica) Cultivars and Defense Response Investigation - Lucia Landi; Annamaria Lucrezia D’Ortenzio; Sarah Mojela Makau; Rita Milvia De Miccolis Angelini; Gianfranco Romanazzi (Journal of Fungi)
Monilinia fructicola is the most common and destructive brown rot agent on peaches. Knowledge of gene expression mediating host–pathogen interaction is essential to manage fungal plant diseases. M. fructicola putative virulence factors have been predicted by genome investigations. The pathogen interaction with the host was validated. Five M. fructicola isolates were inoculated on two cultivars (cv.s) of peach (Prunus persica (L.) Batsch) ‘Royal Summer’ and ‘Messapia’ with intermediate and late ripening periods, respectively. The expression pattern of 17 candidate effector genes of M. fructicola with functions linked to host invasion and fungal life, and seven peach genes involved in the immune defense system were monitored at 0, 2, 6, 10, and 24 h-post inoculation (hpi). All fungal isolates induced similar brown rot lesions on both cv.s whereas the modulation of effector genes was regulated mainly at 2, 6, and 10 hpi, when disease symptoms appeared on the fruit surface, confirming the involvement of effector genes in the early infection stage. Although differences were observed among the fungal isolates, the principal component investigation identified the main differences linked to the host genotype. The salicylic acid and jasmonate/ethylene signaling pathways were differently modulated in the host independent from the fungal isolate used for inoculation. On plants susceptible to brown rot, the pathogen may have adapted to the host’s physiology by modulating its effectors as weapons.